2020
DOI: 10.3390/cells9030560
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes in Breast Cancer, the Thick and the Thin

Abstract: It is well established that breast cancer development and progression depend not only on tumor-cell intrinsic factors but also on its microenvironment and on the host characteristics. There is growing evidence that adipocytes play a role in breast cancer progression. This is supported by: (i) epidemiological studies reporting the association of obesity with a higher cancer risk and poor prognosis, (ii) recent studies demonstrating the existence of a cross-talk between breast cancer cells and adipocytes locally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 158 publications
(196 reference statements)
3
59
1
1
Order By: Relevance
“…We have found that intratumoral adipocyte-high breast cancer enriched for the inflammation, metastasis, and cancer stemness related gene sets, which is in agreement with the previous reports [25,[49][50][51][52]. This was more significant with the ER+/HER2-subtype compared with TNBC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have found that intratumoral adipocyte-high breast cancer enriched for the inflammation, metastasis, and cancer stemness related gene sets, which is in agreement with the previous reports [25,[49][50][51][52]. This was more significant with the ER+/HER2-subtype compared with TNBC.…”
Section: Discussionsupporting
confidence: 92%
“…Cancer-associated adipocytes are known to promote tumor growth, invasion, and migration of breast cancer cells in vitro [25]. To this end, we hypothesized that tumors that were high in intratumoral adipocytes would be associated with the advanced American Joint Commission on Cancer (AJCC) clinical cancer staging in the TCGA cohort.…”
Section: Intratumoral Adipocyte-high Tumors Were Not Associated Withmentioning
confidence: 99%
“…A recent review by Rybinska et al, 2020, showed an increase in TNFα, IL-6, IL-1β, CCL2, adiponectin and collagen and a decrease in leptin in BC causing anorexia leading to cachexia. Furthermore, BC mediated cachexia is also associated with a decrease in adipogenesis transcription factors PPARγ, c/EBPα, GLUT4 and SREBP-1, and an increase in HSL, an enzyme responsible for lipolytic activity in cachexia [235].…”
Section: Cachexiamentioning
confidence: 99%
“…The tumor-provoked hypermetabolism in CC leads to a state of energy imbalance that cannot be recovered through nutritional supplementation (Kir and Spiegelman, 2016;Vaitkus and Celi, 2017). According to morphologic modifications, decreased lipid content and a proinflammatory phenotype, cachectic adipocytes are similar to TAAs (Rybinska et al, 2020). As recently demonstrated, the downregulation of adipogenic and lipogenic genes is affected early in AT, resulting in lipolysis and AT remodeling during CC (Batista et al, 2013;Sun et al, 2020).…”
Section: Tumor-induced Adipose Tissue Remodelingmentioning
confidence: 97%